Corilagin Interferes With Toll-Like Receptor 3-Mediated Immune Response in Herpes Simplex Encephalitis - Li, Lu-Jun; Zhang, Shao-Jun; Liu, Pan; Wang, You-Qin; Chen, Zhi-Lin; Wang, Yu-Jie; Zhou, Jia-Bin; Guo, Yuan-Jin; Zhao, Lei (Frontiers in Molecular Neuroscience, 2019)
Herpes simplex encephalitis (HSE) is the most common infectious disease of the central nervous system worldwide. However, the pathogenesis of HSE is not clear. Research has shown that the immune response mediated by the toll-like receptor 3 (TLR3) signaling pathway is essential to protect the central nervous system against herpes simplex virus (HSV) infection. However, an excessive immune response may cause tissue damage accompanied by pathological changes. The aim of this study was to explore the molecular mechanism via which corilagin controls HSE through the TLR3 signaling pathway in vitro and in vivo. Cells and mice were pre-treated with polyriboinosinic polyribocytidylic acid [poly(I:C)] or HSV type 1, and then treated with corilagin. After treatment, the mRNA and protein levels of TLR3, TLR-like receptor-associated interferon factor (TRIF), tumor necrosis factor (TNF) receptor type 1-associated DEATH domain protein (TRADD), TNF receptor-associated factor (TRAF) 3 and 6, nuclear factor-kappa-B (NF-κB) essential modulator (NEMO), P38, and interferon regulatory factor 3 (IRF3) were decreased. Interleukin-6 (IL-6), TNF-α, and type 1 interferon-β were also decreased. When TLR3 expression was silenced or increased, corilagin still inhibited the expression of TLR3 and its downstream mediators. Hematoxylin-eosin (HE) staining and immunohistochemical examinations of mouse brain tissues revealed that corilagin lessened the degree of brain inflammation. Altogether, these results suggest that corilagin may regulate the immune response in HSE and relieve inflammatory injury by interfering with the TLR3 signaling pathway.